PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO ANIMASI KINEMASTER TERHADAP PENINGKATAN KEMAMPUAN MENULIS KARANGAN NARASI SISWA KELAS VII MTS AL-ITTIHADIYAH MAMIYAI MEDAN - Dila Rizki Amanda; Rina Devianty; Edi Saputra (CAKRAWALA: Journal of Citizenship Teaching and Learning, 2026)
This study is entitled “The Development of Kinemaster Animated Video Learning Media to Improve Narrative Writing Skills of Seventh Grade Students at MTs Al-Ittihadiyah Mamiyai Medan.” The background of this study is based on students’ low writing ability, which is caused by a lack of reading habits and the limited use of learning media that are appropriate to students’ characteristics. This research employed the Research and Development (R&D) method using the ADDIE model (Analyze, Design, Development, Implement, and Evaluate). The research subjects consisted of subject matter experts, language experts, media experts, teachers, and seventh grade students who were divided into two classes, namely the experimental and control classes, with 24 and 22 students respectively. Data collection techniques included observation, interviews, expert validation questionnaires, and writing tests. The results of the study indicate that: (1) the Kinemaster learning media is highly valid, with an average validation score of 95%; (2) the effectiveness test using N-Gain shows that the experimental class obtained an average score of 69.08% in the high category, while the control class obtained an average score of 48.7% in the low category, indicating a significant difference between the two classes; (3) the practicality questionnaire results show that the Kinemaster media achieved a practicality percentage of 98% from teachers and 92% from students, both categorized as very practical. Therefore, the Kinemaster learning media is declared valid, practical, and sufficiently effective in improving students’ narrative writing skills.